2013
DOI: 10.1017/s0954422413000127
|View full text |Cite
|
Sign up to set email alerts
|

Social influences on eating: implications for nutritional interventions

Abstract: We review recent research on the effect of social context on food intake and food choice and assess the implications for nutritional interventions. We focus on studies of modelling of eating behaviour and the impact of perceived eating norms on the amounts and types of food that individuals eat. We suggest that social context influences eating via multiple mechanisms, including identity signalling and self-presentation concerns. However, building on existing theoretical models, we propose that social factors m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 93 publications
4
98
1
1
Order By: Relevance
“…With 32 out of 33 studies, both correlational and experimental, showing evidence of a relation between peer social norms and young people's food intake, this systematic research synthesis corroborates conclusions of previous reviews that social norms can play a role in young people's food intake (Higgs, 2015;Robinson, Blisset, et al, 2013;Robinson, Thomas, et al, 2014). Our quality assessments indicated that the studies were in general of good quality.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…With 32 out of 33 studies, both correlational and experimental, showing evidence of a relation between peer social norms and young people's food intake, this systematic research synthesis corroborates conclusions of previous reviews that social norms can play a role in young people's food intake (Higgs, 2015;Robinson, Blisset, et al, 2013;Robinson, Thomas, et al, 2014). Our quality assessments indicated that the studies were in general of good quality.…”
Section: Discussionsupporting
confidence: 85%
“…Together, these previous syntheses provide clear indications that social norms play a role in food intake (Robinson, Blisset, et al, 2013;Robinson, Thomas, et al, 2014) and provide an account of the (evolutionary) mechanisms explaining why human beings follow social norms related to eating (Higgs, 2015). However, the potential for social norms to improve health behaviour, including food intake, is by no means ubiquitous, with various studies also showing null effects or even negative results (for an overview, see Cameron & Campo, 2006).…”
Section: Towards An Understanding Of Moderatorsmentioning
confidence: 90%
See 1 more Smart Citation
“…This was not surprising given that food choices are socially embedded (Robinson et al, 2013). Other qualitative investigations into factors determining healthy eating have also implied that a major perceived barrier to healthy eating is the competing requirements of other family members (Baruth et al, 2014;Cason-Wilkerson et al, 2015;McGuffin et al, 2015).…”
Section: Perceived Benefits Of and Barriers Toward Personalised Nutrimentioning
confidence: 98%
“…Moreover, there is some research suggesting that having heavier friends increases one's likelihood of gaining weight (Christakis & Fowler, 2007). One potential mechanism explaining this effect is that individuals could use the eating behaviour of their overweight peers as a guide to inform their own behaviour and this in some instances could result in increased energy consumption (Robinson, Blissett, & Higgs, 2013b). Although work has examined how the mere presence of overweight individuals can influence behaviour or activate different stereotypes (Campbell & Mohr, 2011;De Luca & Spigelman, 1979), we are not aware of any work directly examining whether directly manipulating beliefs about what overweight vs. normal/healthy weight individuals have been eating influences the eating behaviour of normal/healthy weight participants.…”
Section: Introductionmentioning
confidence: 99%